R&D consortia in competitive supply chains - CRAMA, Pascale (Institutional Knowledge at Singapore Management University, 2022)
R&D consortia, which coordinate R&D activities of their member firms, have been successful in many industries. We study a model with two competing supply chains each consisting of a manufacturer and a supplier. The manufacturers compete in the final product market, and can conduct R&D to reduce unit product costs of their final products. The R&D can be done in three different ways: by the two manufacturers independently, by them jointly in a horizontal R&D consortium, or by the supplier and the manufacturer jointly in each supply chain in two vertical R&D consortia. We find that as compared to independent R&D, both the horizontal consortium and the vertical consortia lead to higher R&D effort, wholesale prices, and output quantities in the supply chains. However, different supply chain parties’ preferences over the two types of consortia are not necessarily consistent. We then consider a game where the firms endogenously determine to form which type of R&D consortium in the industry. We show that vertical consortia emerge in industries with high R&D uncertainty and effort cost, and the horizontal consortium is likely to emerge otherwise. Our results provide plausible explanations on why different types of R&D consortium emerge and flourish in different industries and shed light on their potential benefits for consumers and social welfare.